Tillage and Nitrogen Placement Effects on Yields in a Short-Season Corn/Wheat/ Double-Crop Soybean Rotation - D. W. Sweeney (Kansas Agricultural Experiment Station Research Reports, 2017)
In 2016, adding nitrogen (N) greatly improved average wheat yields, but the response to tillage and different N placement methods was minimal. Double-crop soybean yields were unaffected by tillage or the residual from N treatments that were applied to the previous wheat crop.
Keywords: tillage; no-till; nitrogen placement; corn; wheat; soybean